Elastic Wave Behaviour in 2-D Acoustic Interface Superlattices of an Altered Phase - KAPELEWSKI, Jerzy; LILA, Bogdan (Archives of Acoustics, 2011)
The purpose of the paper is to outline a systematic and unified non-local treat- ment of mode conversion effects associated with an interface superlattice being a 2D pseudo-array composed of altered phase inclusions (exemplified by impurity clusters) and located at a solid-solid plane interface. It will be illustrated, in some detail, for the instructive case of a Stoneley type acoustic wave (SW), incident on a period- ically nonhomogeneous portion of an interface and partly transformed into bulk modes propagating in one of the component solid. An analytical model scheme is constructed, using a variational method combined with the T matrix approach, ap- propriate for the 2D periodic array treated, and decaying into the depth of this solid for the structure in a way determined by the array geometry and element 3D pro- files as well as the boundary conditions at the interface. An apodization (weighting) to reduce the side-lobes level is incorporated into the structure by appropriately varying lateral dimensions and the depth of particular scatterers.